'Refugee' or 'returnee'? The ethnic geopolitics of diasporic resettlement in China and intergenerational change. Issue 4 (24th September 2012) - Ho, Elaine Lynn‐Ee
<x xml:space="preserve">Abstract</x> The interrelationship between forced migration, return migration and ethnicity remains relatively unexplored in current scholarship. By using the case of China's resettlement policy towards diasporic Chinese descendants expelled from Southeast Asia during 1949–1979 and examining their contemporary situation, this paper highlights the way scholarship on forced migration and ethnically privileged (return) migration can mutually enrich one another. The paper, first, examines the geopolitical context of Chinese forced migration and the premises of China's preferential policy towards co‐ethnics, which labelled the 'refugees' as 'returnees' intentionally. It argues that metaphors of extraterritorial ethnic kinship and 'return' are used to justify ethnic privilege but the co‐ethnics experienced socio‐spatial exclusion in China because of their cultural distinctiveness. Second, the paper explores the impact of the post‐1980s reforms on the rural overseas Chinese farms in which the co‐ethnics were resettled. This discussion suggests that the rescaling of governance brought about policies that capitalise upon their distinctive Southeast Asian identities to reinvent the farms as economic zones and tourism sites. The sustainability of this economic strategy is, however, questioned in the third part of the paper, which considers intergenerational change now happening on the farms. It argues that international migration histories are transitioning to new internal migration flows. Such migration succession trends may transform the ethnically privileged status of the farms and their inhabitants. The qualitative findings in this paper direct broader inquiry into the complex ethnic geopolitics underpinning mobilisations of diasporic belonging and also the implications of intergenerational change.